Geoquímica e índice de geoacumulação de mercúrio em sedimentos de superfície do estuário de Santos - Cubatão (SP) - Luiz-Silva, Wanilson (2002)
The concentrations of mercury in surface sediments (<63mum fraction) from Santos-Cubatão Estuary, located in State of São Paulo, southeast Brazil, were determined to obtain the level of contamination in this highly polluted area. Fifteen stations distributed though seven rivers were sampled (156 samples collected) from September 1997 to August 1998 (12 stations sampled monthly) and during March, June, September and December 1998 (three stations sampled quarterly). The levels of mercury varied from 0.10 to 6.77 ppm, with the index of geoaccumulation of the rivers varying between grades 1 and 3 (annual average). The Cubatão is the most polluted river and the main agent of Hg dispersion in the study area. Geochemical data revealed that Hg levels in surface from Santos-Cubatão Estuary at present are as elevated as in past (for instance, by comparison 1980's), when Cubatão city was known as one of the most polluted cities in the world.